Escherichia coli K-12 mutants deficient in uracil-DNA glycosylase. - Duncan, B K (1978)
A new assay specific for uracil-DNA glycosylase is described, Escherichia coli mutants partially and totally deficient in uracil-DNA glycosylase activity have been isolated by using this assay in mass-screening procedures. These have been designated ung mutants. The ung gene maps between tyrA and nadB on the E. coli chromosome. T4 phage containing uracil in their DNA grow on the most glycosylase-deficient hosts but are unable to grow on wild-type bacteria. This provides a simple spot test for the ung genotype. The ung mutants show slightly higher rates of spontaneous mutation to antibiotic resistance. Taken together, these results suggest a central role for uracil-DNA glycosylase in the initiation of an excision repair pathway for the exclusion of uracil from DNA.